Cosmogonic Sacrifice - Aḥmadī, Amīr (Indo-Iranian journal, 2017)
A number of prominent scholars of Zoroastrianism have recently taken up Marijan Molé’s thesis that Ahura Mazdā created the world by way of a sacrifice. This article examines the sources that have been adduced for the thesis. It concludes that neither in Avestan nor Pahlavi texts do we find any evidence for the supposed cosmogonic sacrifice.